The Nursing Leadership Institute program evaluation: a critique - Havaei F; MacPhee M (Dove Medical Press, 2015)
Farinaz Havaei, Maura MacPhee School of Nursing, University of British Columbia, Vancouver, BC, Canada Abstract: A theory-driven program evaluation was conducted for a nursing leadership program, as a collaborative project between university faculty, the nurses' union, the provincial Ministry of Health, and its chief nursing officers. A collaborative logic model process was used to engage stakeholders, and mixed methods approaches were used to answer evaluation questions. Despite demonstrated, successful outcomes, the leadership program was not supported with continued funding. This paper examines what happened during the evaluation process: What factors failed to sustain this program? Keywords: leadership development, theory-driven evaluation, mixed methods, collaborative logic modeling